Comparison Effect of Leaves and Bark Extract of Eucalyptus (Melaleuca leucadendra), Sappan (Caesalpinia sappan), and Cinnamon (Cinnamomum zeylanicum) to Reduce Streptococcus mutans Biofilm Formation - Utami, Trianna Wahyu; Ekananda, Bernadetha Nathania; Anjani, Yasmin Regita; Listyarifah, Dyah; Nur, Asikin; Syahbudin, Atus (Faculty of Dentistry, Universitas Gadjah Mada, 2023)
To evaluate the effect of eucalyptus, sappan, and cinnamon leaf and bark extract on the percentage of S. mutans biofilm formation. The test group was divided into a negative control (1% Dimethyl sulfoxide), a treatment group (eucalyptus, sappan, and cinnamon leaves and bark at concentrations of 50%, 25%, and 12.5%, respectively), and a positive control (0.2% chlorhexidine). Each concentration of eucalyptus, sappan, and cinnamon leaves and barks extract, Brain Heart Infusion Broth (BHI-B), bacteria according to the McFarland 0.5 standard, a positive control, and a negative control were added to a 96-well microplate. They were incubated at 37 °C for twenty-four hours before being rinsed with phosphate buffer saline (PBS) and stained with 0.1% crystal violet. The optical density was then measured using a microplate reader with a 540 nm wavelength. The absorbance value is then factored into the percentage of bacterial adhesion inhibition formula. A statistical test revealed a significant difference (p < 0.05) in the percentage of inhibition between the three extracts of leaves and bark and the negative control group (1% DMSO). There is a significant difference between all leaves and barks concentration and the positive control group except the 50% concentration of sappan leaf group and 50% concentration of cinnamon leaf group. The sappan leaf and cinnamon leaf at 50% concentration exhibit no significant difference (p > 0.05) with the positive control. Eucalyptus, sappan, cinnamon leaves and barks at a concentration of 50% demonstrated effectiveness of the extractant in inhibiting the formation of biofilm masses by S. mutans in comparison with the other group.